To Get Connected to the World Through a Different Channel. Wojciech Bruszewski’s Textual Machines - Załuski, Tomasz ((Dif)fusions: Relations between Literature and Art in Poland after 1945, 2019)
The article proposes an analysis of media experiments with the word and language in Wojciech Bruszewski’s artistic theory-practice. The artist presumed that the language and the culture of the word were factors which determined traditional way of using technical media and reduced the image they created to a schematic, culturally conditioned artifact, capable of providing only partial access to the world. In order to unlock the media from conceptual conventions and structures of experience shaped by the culture of the word, and thereby to produce a different, extended image of the world, it is necessary to remediate the word as such. Bruszewski took the word at the level of its infrastructure and treated it as an anagrammatic audio-visual aggregate. He kept on constructing more and more complex machines which generated new combinations of letters and words as well as created new rules for translating the visual and the audial, and finally, he wrote ‘documental fictions’ which recombined fragments of individual biography and world history. In this way, he evoked generative chaos as reality which exceeds conceptual schemes of the humanistic culture of the word.